If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(4n + 3) = 8 Reorder the terms: -4(3 + 4n) = 8 (3 * -4 + 4n * -4) = 8 (-12 + -16n) = 8 Solving -12 + -16n = 8 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -16n = 8 + 12 Combine like terms: -12 + 12 = 0 0 + -16n = 8 + 12 -16n = 8 + 12 Combine like terms: 8 + 12 = 20 -16n = 20 Divide each side by '-16'. n = -1.25 Simplifying n = -1.25
| 3x-6+2=5x-6 | | 3x=26.25 | | 5(x+4)=3(2x-1) | | .7(.1x+.1)=-.7 | | 14(v+2)-2v=4(3v+3)-18 | | x+31=-48 | | (3x-1)(2x^2+3x-3)=0 | | 9.5-23.5p=3.5(9p+3) | | (5v-6)(5+v)=0 | | 10x+6y+6+17x-16y-16= | | 4(y+3)-3=25 | | 11(z+1)-3(z-1)=3(z-2)+4(z-3) | | 9x-2(-5+7)=-8x-5 | | 4(9-14)=n-3 | | 67-5*7= | | (x+1)3=216 | | -0.04x^2+0.64x+1.94=0 | | (3x-2)(2x+6)=0 | | 9x-(8x+9)=9x-33 | | 30y+8=32 | | (2-x)(2+x)=0 | | 5=9x-8x+6 | | (7-x)(x^2+2x-3)=0 | | 6(6-4)=12y | | x+27=-52 | | x^2=128-8x | | 11x^2+2x=10 | | (7a^2-2a+6)-(-5a^2+3)=0 | | 3x+8(x-1)=0 | | -9.9-26.7=6.1-24.7r | | D^2+3d+4=0 | | 4x^2+7x+3=6 |